Good families of Barcelona : a social history of power in the industrial era - McDonogh, Gary W. (Princeton, New Jersey : Princeton University Press, 1986)
Gary McDonogh combines ethnology and history to analyze the organization, reproduction, and decline of an urban industrial elite. Using Barcelona as the foundation for more general consideration of power-holding groups, he tells the story of the Good Families," those few hundred lineages who have dominated the city in the nineteenth and twentieth centuries. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- List of Illustrations -- List of Tables -- Preface -- A Note on Names and Transcriptions -- Chapter I. Introduction -- Chapter II. Barcelona in Historical Perspective -- Chapter III. Family and Variation in Catalonia -- Chapter IV. La Casa Industrial: Household and Company in the Industrial Elite -- Chapter V. From Family to Oligarchy: The Cohesion of Economic Power -- Chapter VI. Pigs And Gentlemen: The Education of an Elite -- Chapter VII. Commercium and Connubium -- Chapter VIII. The Family and the City: Power and the Creation of Cultural Imagery -- Chapter IX. Family, Agency, and Networks of Power: Towards a Comparative Understanding of Elites -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Elite (Social sciences) -- Spain -- Barcelona -- History; Kinship -- Spain -- Barcelona -- History; Power (Social sciences) -- History; Barcelona (Spain) -- Social conditions; Élite (Sciences sociales) -- Espagne -- Barcelone -- Histoire; Parenté -- Espagne -- Barcelone -- Histoire; SOCIAL SCIENCE -- Sociology -- General; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Elite (Social sciences); Kinship; Power (Social sciences); Social conditions; Spain -- Barcelona; History